2010
DOI: 10.4093/kdj.2010.34.5.303
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Diet in Good and Poor Glycemic Control Groups in Elderly Patients with Type 2 Diabetes Mellitus

Abstract: BackgroundIdentification of dietary patterns is important for glycemic management in elderly patients with type 2 diabetes mellitus (T2DM).MethodsElderly T2DM patients (> 65 years of age, n = 48) were categorized based on their concentration of glycated hemoglobin (HbA1c). Subjects with HbA1c levels below 7% were placed in the good control (GC) group and those with HbA1c levels equal to or above 8% were placed in the poor control (PC) group. Anthropometric data, blood parameters, and dietary intake records wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…As expected, the results of the present study showed a significant positive association between higher calorie intake and increased HbA1c, even after adjustment for total energy intake. A previous cross‐sectional Korean study and two prospective studies obtained similar results, though the sample sizes were small. In contrast, both JDCS and J‐EDIT found no correlation between the carbohydrate energy ratio and HbA1c.…”
Section: Discussionsupporting
confidence: 64%
“…As expected, the results of the present study showed a significant positive association between higher calorie intake and increased HbA1c, even after adjustment for total energy intake. A previous cross‐sectional Korean study and two prospective studies obtained similar results, though the sample sizes were small. In contrast, both JDCS and J‐EDIT found no correlation between the carbohydrate energy ratio and HbA1c.…”
Section: Discussionsupporting
confidence: 64%
“…In a study that examined nutritional intakes in good (GC) and poor (PC) glycemic control groups in elderly Korean patients with type 2 diabetes mellitus, the distribution of macronutrients differed significantly between GC group (%E of protein : %E of fat : %E of carbohydrate = 19:22:62) and PC group (%E of protein : %E of fat : %E of carbohydrate = 15:15:71). This result shows that the PC group had higher carbohydrate intake compared with the GC group 15 . Furthermore, negative correlations between HbA1c levels and protein or fat intake were also observed.…”
Section: Discussionmentioning
confidence: 63%
“…The Korean study showed the significant positive correlation of %E of carbohydrate with the exacerbation of HbA1c 15,16 . However, %E of carbohydrate in Korean elderly diabetic patients was substantially high.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations